2019
DOI: 10.1002/capr.12267
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory examination of clinician perspectives on positive memories and post‐traumatic stress disorder interventions

Abstract: Despite the role of positive memories in the aetiology and maintenance of post-traumatic stress disorder (PTSD), most PTSD interventions primarily focus on traumatic memories. To aid the development of a PTSD-specific technique focused on processing positive memories, we gathered formative input from practicing clinicians on the content, format, feasibility and acceptability of this proposed intervention technique. We recruited licensed clinicians (n = 46) through professional networks and psychology organisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
(89 reference statements)
0
10
0
Order By: Relevance
“…Still, other clinicians may never assess for or address positive internal experiences in PTSD treatment; perhaps, clinicians conceptually link trauma with negative internal experiences and do not consider the influence of processing positive internal experiences on distress (Lyubomirsky et al, 2006). Recent research indicates that trauma-exposed clients (Caldas et al, 2020) and trauma clinicians (Contractor, Caldas, et al, 2019) are willing and interested in discussing more positive internal experiences (positive memories in particular) during treatment, which provides an impetus for future research to explore ways in which positive internal experiences are actually addressed in practice (e.g., by reviewing audio transcripts of PTSD sessions provided by clinicians in the community).…”
Section: Discussionmentioning
confidence: 99%
“…Still, other clinicians may never assess for or address positive internal experiences in PTSD treatment; perhaps, clinicians conceptually link trauma with negative internal experiences and do not consider the influence of processing positive internal experiences on distress (Lyubomirsky et al, 2006). Recent research indicates that trauma-exposed clients (Caldas et al, 2020) and trauma clinicians (Contractor, Caldas, et al, 2019) are willing and interested in discussing more positive internal experiences (positive memories in particular) during treatment, which provides an impetus for future research to explore ways in which positive internal experiences are actually addressed in practice (e.g., by reviewing audio transcripts of PTSD sessions provided by clinicians in the community).…”
Section: Discussionmentioning
confidence: 99%
“…Current study findings have important clinical implications. Prior research indicates that trauma‐exposed clients (Caldas, Jin, Dolan, Dranger, & Contractor, 2020) and trauma clinicians (Contractor, Caldas, Dolan, Banducci, & Jin, 2020) are willing and wish to therapeutically address positive memories in PTSD treatment. Consistent with this trend, a recent review indicated that positive memories and positive emotions are addressed as clinical targets and mechanisms in a few PTSD interventions (Contractor, Weiss, Forkus, & Keegan, in press).…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, PPMT may address diverse client needs, goals, and symptom profiles with flexibility. Lastly, clinicians endorse practicality, ease of learning, and positive impact on therapy satisfaction/tolerability of positive memory processing (Contractor et al, in press), and clients endorse willingness to participate in positive memory-oriented sessions, perceive feasibility and acceptability of incorporating positive memory strategies into treatment, and anticipate increased satisfaction/tolerability of trauma-focused therapy with an integrated positive memory component (Caldas et al, 2020).…”
Section: Discussionmentioning
confidence: 99%